Study on the Soil Fertility and Mapping in Ramasamudram-1 Microwatershed of Yadgir Taluk and District of Karnataka, India - Hegde, Rajendra; Kumar, Mahendra; K. V, M. B. Niranjana; K. V., Seema; B. A., Dhanorkar (International Journal of Bio-resource and Stress Management, 2021)
An investigation was under taken to study the soil fertility status of major nutrients, micronutrients and mapping in Ramasamudram-1 microwatershed of Yadgir taluk and district of Karnataka, India during the year 2019. Total seventy-four grid wise surface soil samples were collected at 320 m grid interval at 0-15 cm depth to assess the soil parameters (texture, pH, EC, OC, available P, K, S, Zn, Cu, Fe, Mn and B) and prepare the soil fertility maps through GIS using Kriging method. The results of the study indicated that, the texture of the soil varied from loamy sand to sand clay loam in surface. Soil reaction varied from acidic to neutral with non-saline in nature. The distribution of soil organic carbon (32%), available phosphorous (56%) and potassium (47%) status was found to be medium in most of the area of microwatershed. The available sulphur status was found to be low (57%) in maximum area of the microwatershed. The available zinc status was found to be sufficient (46%) in majority area of the microwatershed. The available copper, iron and manganese status of the soils were sufficient (58%) in entire area. Whereas available boron status was found to be low (57%) in maximum area of the microwatershed. Therefore, the study showed that, the soils of the microwatershed were medium in fertility status. There is need of proper fertilizer recommendation and soil management practices can be made productive thereby, increasing the crop yield.